Quantitative proteomic data of flotillin-2 interactome within detergent resistant membranes of HeLa cells - Anita Hryniewicz-Jankowska; Michał Tracz; Ilona Opiełka; Katarzyna Augoff; Aleksander Czogalla; Aleksander F. Sikorski (Data in Brief)
Flotillin-binding protein networks serve as scaffolds, organizing lipid rafts and facilitating the recruitment of other raft-associated proteins such as receptors and downstream signaling molecules to regulate various intracellular pathways, including those involved in cell proliferation, migration, and endocytosis.Flotillins belong to the SPFH (stomatin/prohibitin/flotillin/HflK/C) domain-containing protein family, also known as the prohibitin homology (PHB) domain, which enables membrane association via acylation and hydrophobic hairpin motifs that anchor them to the inner leaflet of the plasma membrane. The functional diversity of flotillin proteins within membrane microdomains primarily stems from their interactions with other proteins.Data presented in this article characterize the proximal interactome of flotillin-2 within detergent-resistant membranes (DRMs) using BioID, a proximity-dependent biotinylation technique. Flotillin-2 was fused with the biotin ligase BirA* at either the N- or C-terminus and expressed in HeLa cells. DRMs were isolated through sucrose density gradient ultracentrifugation, and biotinylated proteins were purified using biotin–avidin affinity followed by label-free quantitative (LFQ) mass spectrometry.This approach identified a set of proteins significantly enriched in DRM fractions from cells expressing flotillin-2–BirA* fusions compared to control cells expressing BirA*–mEGFP. The two analyses allowed for relative quantification of ∼433 and ∼926 unique proteins across the N-terminal and C-terminal BirA* fusions, respectively. 28 (N-terminal) and 88 (C-terminal) proteins were observed as significantly enriched in flotillin-2 samples (28 and 43 with fold change ≥ 2). These enriched proteins are candidate interactors of flotillin-2 within membrane raft domains. Notably, the N-terminal fusion-associated proteins were significantly linked to specific biological processes such as dendritic transport and regulation of signal transduction, whereas the C-terminal fusion group showed enrichment in membrane biogenesis-related proteins. Among here presented DRM partners of flotillin-2, both previously known and earlier unreported interactors of this protein were found. Overall, our BioID-based analysis provides valuable insight into the flotillin-2 interactome in DRM fractions and lays the groundwork for future studies exploring the regulation of membrane lateral heterogeneity and the role of flotillin-mediated domains in signaling pathways, particularly those dysregulated in diseases such as cancer.